1998
DOI: 10.1128/cdli.5.6.784-789.1998
|View full text |Cite
|
Sign up to set email alerts
|

Extracellular and Cytosolic Iron Superoxide Dismutase from Mycobacterium bovis BCG

Abstract: Two forms of iron superoxide dismutase (SOD) were purified from cell extract (CE) and culture filtrate (CF) of Mycobacterium bovis BCG, respectively. The molecular weight of both enzymes was estimated to be approximately 84,000 by gel filtration, whereas that of their subunits was 21,500, as determined by sodium dodecyl sulfate-polyacrylamide gel electrophoresis, indicating that each of purified enzymes is composed of four identical subunits. The specific activities of CE SOD and CF SOD were 3,850 and 4,040, r… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
8
0

Year Published

2006
2006
2018
2018

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 13 publications
(8 citation statements)
references
References 31 publications
0
8
0
Order By: Relevance
“…Evidence of mycobacterial proteins changing subcellular location [ 31 ], may have an impact on the overall topographical classification of epitopes, and indicates the need to take experimental parameters into greater consideration. With this caveat in mind, the highest EDI 1 values for topology categories are seen in the extracelluar (11.49) and cytoplasmic (8.09) proteins (Figure 2b ).…”
Section: Resultsmentioning
confidence: 99%
“…Evidence of mycobacterial proteins changing subcellular location [ 31 ], may have an impact on the overall topographical classification of epitopes, and indicates the need to take experimental parameters into greater consideration. With this caveat in mind, the highest EDI 1 values for topology categories are seen in the extracelluar (11.49) and cytoplasmic (8.09) proteins (Figure 2b ).…”
Section: Resultsmentioning
confidence: 99%
“…Certain species express Mn- or Fe-containing SODs that are secreted to help defend against the O 2 •– burst of the host. In some cases, the Mn or Fe-SOD can work together with SodC to maximize oxidative stress defense as has been shown in M. tuberculosis and related Mycobacterium , , as well as in spores of Bacillus anthracis , the causative agent of anthrax . In other cases, the bacterium lacks an obvious SodC and the Mn- or Fe-SOD is the sole defense against extracellular O 2 •– .…”
Section: Bacterial Pathogensmentioning
confidence: 99%
“…Although most studies propose a cytoplasmic location for SODs, their secretion by some organisms, such as Mycobacterium avium and M . bovis BCG, has been reported . In a former study, we found that FeSOD is immunogenic in the surface immunoproteome of B. pertussis .…”
Section: Discussionmentioning
confidence: 64%
“…The function of SODs is to scavenge superoxide radicals to molecular oxygen or hydrogen peroxide in order to protect organisms against oxidative stress (32). Although most studies propose a cytoplasmic location for SODs, their secretion by some organisms, such as Mycobacterium avium and M. bovis BCG, has been reported (32,33). In a former study, we found that FeSOD is immunogenic in the surface immunoproteome of B. pertussis (15).…”
Section: Discussionmentioning
confidence: 89%